Possibilities of target neurotrophic therapy of ischemic stroke - Lychko, Volodymyr (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
The study aimed to comprehensively investigation the features of changes in the structural and functional characteristics of the brain tissue, cytokine profile, and β-adrenergic reception in the acute period of ischemic stroke (IS) to optimize treatment. Materials and methods. EHF dielectrometry was used to measure the complex dielectric conductivity (CDC) of peripheral blood erythrocytes in patients with IS. Changes in the osmotic resistance of erythrocytes (ORE) under the action of β-adrenergic blockers (β-AB) were determined by photoelectron colourimetry. Plasma levels of interleukin (IL)-6 and tumour necrosis factor (TNF)-α were assessed using an enzyme-linked immunosorbent assay. The basis of the work was the materials of a comprehensive examination of 350 patients with the first in life IS in the dynamics of treatment with human cryopreserved cord blood serum (CCBS). Results. In patients with IS, from the first hours of the development of the disease, there is a sharp increase in the levels of proinflammatory cytokines IL-6 and TNF-α in the blood serum (by 9.3 and 3.9 times, respectively). At the onset of IS, there is a significant increase in the level of β-ARM by 2.4 times as compared with the control and a decrease in CDC by 10.0 % after exposure to an adrenaline solution. The maximum levels of β-ARM (42.43 ± 3.64 CU) are observed in patients with initially severe disease. The established direct correlations between plasma levels of IL-6, TNF-α and β-ARM (r     0.73; p < 0.05 and r = +0,86; p < 0.05, respectively); IL-6, TNF-α and total clinical score on the NIHSS scale (r = +0.895; p < 0.05 and r = +0.9; p < 0.05, respectively). Conclusions. The study has demonstrated the positive immunomodulatory and membrane-protective effects of human CCBS in the acute period of IS. Stabilization of the absolute values of CDC indicated changes in the levels of cell hydration, causing the activation of not only the membrane receptor complex (MRC) of erythrocytes but also an increase in the functional characteristics of the sympathoadrenal system (SAS). The use of CCBS caused a more significant and rapid decrease in the concentrations of the central proinflammatory cytokines IL-6 and TNF-α, which indicated the regulatory effect of the drug in suppressing the local inflammatory response initiated by hypoxia.